RESOURCE POTENTIAL IN INVESTMENT SECURITY OF AGRICULTURAL ENTERPRISES - Levandivskyi , O.T.; Balaniuk , I. F.; Matkovsky , P. Ye.; Matskiv , V.V. (The actual problems of regional economy development, 2023)
A necessary condition for the sustainable development of agricultural enterprises is the accumulation of resource potential, and the level of its formation and use is one of the most important indicators of the development of the country's economy as a whole. Agricultural enterprises are an economically and socially important segment of agricultural production, however, during the period of Russian military aggression against Ukraine, they remain unattractive to most investors. The formation of the resource potential of agriculture and the growth of its investment attractiveness are restrained by an acute shortage of financial resources, an underdeveloped material and technical base, and a low solvent demand of the population. Financial resources are one of the main factors of ensuring the economic development of agricultural enterprises, improving the quality of the technical and technological base. It was determined that the decisive role in the formation of the resource potential of agricultural enterprises should belong to structural transformations and improvement of economic relations. It has been proven that the implementation of an effective strategy for the formation of the resource potential of agricultural enterprises is a systemic problem and requires a comprehensive solution to the following problems: increasing the level of state and regional financing of agricultural enterprise support programs; increasing the effectiveness of regional and sectoral agricultural science and creating a powerful package of competitive innovations (new agricultural and biotechnologies); breeding achievements in plant and animal breeding, modern technical complexes adapted to the conditions of a specific soil and climate zone); formation of economic mechanisms for stimulating the demand of agricultural enterprises for innovative products in the field of material and technical support; creation of a flexible modern regional agro-service infrastructure capable, together with the corresponding national infrastructure, of ensuring the introduction of new elements of material and technical support of agricultural production into the production process.